2011
DOI: 10.1002/eji.201141801
|View full text |Cite
|
Sign up to set email alerts
|

NHERF1 regulates gp120‐induced internalization and signaling by CCR5, and HIV‐1 production

Abstract: The scaffolding protein Na 1 /H1 exchanger regulator factor 1 (NHERF1) plays an important role in the trafficking of G protein-coupled receptors. We previously demonstrated that NHERF1 is involved in chemokine receptor CCR5 homodimer internalization and signal transduction. Given the importance of CCR5 internalization during HIV-1 infection, we evaluated NHERF1's contribution in HIV-1 infection. We challenged human osteosarcoma cells coexpressing CD4 and CCR5 cells expressing either NHERF1 fragment domains or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Because HIV-1 Tg rats lack these replicative elements, this study demonstrates that non-replicative viral elements also profoundly change tissue lipid concentrations as well as membrane phospholipid composition. This is in agreement with studies that reported that the gp120, Env and nef non-replicative elements of the HIV-1 protein interact with plasma membranes, cause localized changes in lipid composition and disrupt cell protein trafficking and signaling [26, 48, 49, 28, 29], consistent with in vitro evidence of increased N-methyl-D-aspartate receptor clustering in lipid microdomains caused by the gp-120 element of the virus [50]. Identifying and targeting non-replicative viral elements that cause membrane lipid disruptions may improve the clinical efficacy of antiretroviral drugs, particularly those that interfere with the membrane phospholipid clustering assembly of the virus and its entry into the host cell [51].…”
Section: Discussionsupporting
confidence: 92%
“…Because HIV-1 Tg rats lack these replicative elements, this study demonstrates that non-replicative viral elements also profoundly change tissue lipid concentrations as well as membrane phospholipid composition. This is in agreement with studies that reported that the gp120, Env and nef non-replicative elements of the HIV-1 protein interact with plasma membranes, cause localized changes in lipid composition and disrupt cell protein trafficking and signaling [26, 48, 49, 28, 29], consistent with in vitro evidence of increased N-methyl-D-aspartate receptor clustering in lipid microdomains caused by the gp-120 element of the virus [50]. Identifying and targeting non-replicative viral elements that cause membrane lipid disruptions may improve the clinical efficacy of antiretroviral drugs, particularly those that interfere with the membrane phospholipid clustering assembly of the virus and its entry into the host cell [51].…”
Section: Discussionsupporting
confidence: 92%
“…Binding of HIV gp120 to chemokine receptors CXCR4 and CCR5 in lymphocytes and macrophages also leads to induction of MAPK [64], [65], [66], [67]. We have shown that polarized oral epithelial cells express to β1 and ϖ integrins, and CCR5 and CXCR4 [44], [46], [68], indicating availability of HIV tat and gp120 receptors in oral epithelium.…”
Section: Resultsmentioning
confidence: 73%
“…NHERF1 enhances chemokine (C-C motif) receptor 5 (CCR5) endocytosis and b-arrestin1 recruitment, thereby promoting the activation of ERK, Rho, and focal adhesion kinase signaling pathways, as well as potentially contributes to CCR5-mediated HIV-1 entry (Hammad et al, 2010;Kuang et al, 2012). NHERF1 overexpression also rescues the endocytosis of an internalization-defective platelet-activating factor receptor and antagonizes platelet-activating factor receptor-mediated inositol phosphate formation .…”
Section: Membrane-associated Guanylate Kinase With Inverted Orientatimentioning
confidence: 99%
“…CCR5 functions as a coreceptor for HIV-1 viral entry into mammalian cells by functioning as a cofactor for the entry of the virus (Henrich and Kuritzkes, 2013). NHERF1 interactions with CCR5 function to enhance actin filament rearrangement of host cells, a function that is essential to allow postcell entry HIV-1 replication (Hammad et al, 2010;Kuang et al, 2012). PDZK1 interactions with hIPR selectively facilitate hIPRdependent activation of endothelial migration and vascular angiogenesis in vitro (Turner et al, 2011).…”
Section: Role Of Pdz Proteins In Gpcr-regulated Physiologymentioning
confidence: 99%